User Insights: Understanding the Acceptance and Utilization of the National Health Insurance Mobile Application - Pratiwi Hanjani Putri; Michelle Steenvoorden (Journal of Health Innovation and Environmental Education, 2025)
Purpose of the study: to analyze the factors that influence user acceptance of the National Health Insurance Mobile application using the Unification Theory Model of Technology Acceptance and Use. Methodology: The population of this study was users of the National Health Insurance Mobile application residing in Jakarta, Bogor, Depok, Tangerang, and Bekasi. Questionnaires were distributed online and offline, and the sample collection technique used multi-stage purposive sampling. This study employed quantitative methods and CB-SEM analysis techniques. Data analysis was carried out using AMOS version 24. Main Findings: The results showed the rejection of seven of the twelve hypotheses tested. The results of this study are expected to provide recommendations for the development of a National Health Insurance Mobile application for the Social Health Insurance Administration Agency. Novelty/Originality of this study: This study offers new insights into how users accept and utilize the National Health Insurance mobile application by integrating behavioral, experiential, and system-related factors in a single analytical model. It advances current knowledge by identifying specific user-driven barriers and facilitators, providing evidence-based directions for improving digital health service adoption and optimizing user engagement.